Concentrations and properties of ice nucleating substances in exudates from Antarctic sea-ice diatoms. Issue 2 (19th January 2021) - Xi, Yu; Mercier, Alexia; Kuang, Cheng; Yun, Jingwei; Christy, Ashton; Melo, Luke; Maldonado, Maria T.; Raymond, James A.; Bertram, Allan K.
Abstract : Field Antarctic sea-ice diatom supernatant samples showed ice nucleating abilities. Abstract : The ocean contains ice nucleating substances (INSs), some of which can be emitted to the atmosphere where they can influence the formation and properties of clouds. A possible source of INSs in the ocean is exudates from sea-ice diatoms. Here we examine the concentrations and properties of INSs in supernatant samples from dense sea-ice diatom communities collected from Ross Sea and McMurdo Sound in the Antarctic. The median freezing temperatures of the samples ranged from approximately −17 to −22 °C. Based on our results and a comparison with results reported in the literature, the ice nucleating ability of exudates from sea-ice diatoms is likely not drastically different from the ice nucleating ability of exudates from temperate diatoms. The number of INSs per mass of DOC for the supernatant samples were lower than those reported previously for the sea surface microlayer and bulk sea water collected in the Arctic and Atlantic. The INSs in the supernatant sample collected from Ross Sea were not sensitive to temperatures up to 100 °C, were larger than 300 kDa, and were different from ice shaping and recrystallization inhibiting molecules present in the same sample. Possible candidates for these INSs include polysaccharide containing nanogels. The INSs in the supernatant sample collected from McMurdo Sound were sensitive to temperatures of 80 and 100 °C and were larger than 1000 kDa. Possible candidates for these INSs include protein containing nanogels.